(untitled) (Global Journal of Human-Social Science, 2018)
This study aims to identify the status of AIDS patients in Jordan and their social and economic characteristics through detecting number of the cases and ways of contracting this disease The patients were classified according to age gender place of contracting the disease and their origin The study came with the following results